ALGORITHMIC PROCEDURES FOR CONSTRUCTING ONTOLOGICAL REPRESENTATIONS OF PRODUCTION TECHNOLOGIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
This paper focuses on formalized description of technologies as a category of procedural knowledge. It describes the model of ontological representation of technologies. The authors present the algorithms of staged combined design of unified decomposition constructions that enable to form decomposition structures of technologies. The article introduces the extended algorithm to construct ontological representation of technologies.